2021
DOI: 10.3390/min11101065
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Optimization of Gold Ore Flotation Circuit via Linear Circuit Analysis and Mass Balance Simulation

Abstract: The aim of this study is to diagnose and optimize a closed multistage gold ore flotation circuit in an operational industrial plant. Linear circuit analysis (LCA), a partition-based model, and a mass balance model using flotation first-order kinetics are employed to diagnose the current process. The result shows that the current circuit operates with high recovery but the gold grade of the final concentrate is low owing to the low buoyancy ratio. Hence, several alternative circuits with different streamlines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
2
0
3
Order By: Relevance
“…휘수연석에 소수화 강화를 위해 비이온성 포수제인 등 유를 포수제로 활용하였다 4,6,14) . 광액의 분산성 향상 및 맥 석인 규산염광물의 부유 억제를 위해 규산나트륨을 억제 제로 선택하였다 15) .…”
Section: Sem-edsunclassified
See 2 more Smart Citations
“…휘수연석에 소수화 강화를 위해 비이온성 포수제인 등 유를 포수제로 활용하였다 4,6,14) . 광액의 분산성 향상 및 맥 석인 규산염광물의 부유 억제를 위해 규산나트륨을 억제 제로 선택하였다 15) .…”
Section: Sem-edsunclassified
“…광액의 분산성 향상 및 맥 석인 규산염광물의 부유 억제를 위해 규산나트륨을 억제 제로 선택하였다 15) . 기포제는 폴리프로필렌 계통의 AF65 를 사용하였다 6) . 부유선별 실험 조건은 선행연구를 참고 하여, 등유 150 g/t, AF65 75 g/t, 규산나트륨 1000 g/t로 설정하였으며, 몰리브덴 원광 500g, 광액농도 30 v/v%로 수행하였다 4,6,14,16) .…”
Section: Sem-edsunclassified
See 1 more Smart Citation
“…Existing flotation plants need simple but effective tools for diagnosis and optimization as the mined sulphide ore becomes more complex and lean of valuable minerals. In this Special Issue, a study by Han et al [11] showed that linear circuit analysis (LCA) and mass balance (MB) simulation are simple yet powerful tools that can be used to diagnose and optimize the gold ore flotation circuit. From their simulation results, they showed that the current process flotation circuit can be changed to an alternative circuit to obtain the current recovery while improving the gold grade of the concentrate by 128%.…”
Section: Flotationmentioning
confidence: 99%
“…Obviously, for the ore of the technological sample of the deposit, a combined enrichment scheme, including gravity processes for capturing free gold, will be more promising, and flotation to recover fine free gold and gold associated with sulfide minerals. In relation to the above problems, it was decided to stop prospecting experiments on the original ore and continue research on flotation on gravity tailings [31].…”
Section: Investigation Of the Deposit Ore Dressability By Flotation M...mentioning
confidence: 99%